Layanan Guru BK Untuk Siswa Mengalami Grieving Di Madrasah Tsanawiyah Negeri 1 Pontianak - Rizka Dinda Aulia; Nabila Syawa Ramadhania; Adinda Aulia Nur Kamil (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2026)
This study aims to explore cases of grief (grieving) in students at MTs Negeri 1 Pontianak, analyze the suitability of their responses with the stages of grieving according to the Kubler-Ross theory, and observe the service process carried out by Guidance and Counseling (BK) Teachers. Losing parents during adolescence has a significant impact on students' psychological well-being. The research method used is qualitative with a case study approach to 3 (three) female students who experienced the loss of parents (orphans). Data collection was carried out through in-depth interviews with BK teachers, structured observations of student behavior, and documentation. Data analysis used the Miles & Huberman model with triangulation validity techniques. The results of the study showed that the three female students went through stages of grieving including denial, anger, bargaining, depression, and acceptance with different intensities and durations: dramatic to attract attention, withdrawing from the social environment, hiding sadness while appearing strong, expressing emotions through social media. Each student exhibits unique coping strategies. MR tends to seek and create attention through social media with a pattern of cell phone dependency. NK channels emotions through writing with signs of physical restlessness, while TS focuses on extracurricular activities while maintaining emotional distance. The study found that school counseling services are still informal and unstructured, unable to detect and accompany the grieving process consistently. The findings emphasize the importance of developing systematic counseling services that are sensitive to the emotional needs of grieving students, as well as structured individual and group counseling programs